Characterization of heat tolerance in wheat cultivars and effects on production components1 - PIMENTEL, ADERICO JUNIOR BADARO (Revista Ceres, 2015)
There is a need for heat tolerant wheat cultivars adapted to the expansion of cultivation areas in warmer regions due to the high demand of this cereal for human consumption. The objective of this study was to evaluate the effect of high temperatures on grain yield and yield components of wheat and characterize heat tolerant wheat genotypes at different development stages. The genotypes were evaluated in the field with and without heat stress. High temperatures reduced the number of spikelets per spike (21%), number of grains per spike (39%), number of grains per spikelet (23%), 1000-grain weight (27%) and grain yield (79%). Cultivars MGS 1 Aliança, Embrapa 42, IAC 24-Tucuruí and IAC 364-Tucuruí III are the most tolerant to heat stress between the stages double ridge and terminal spikelet; MGS 1 Aliança, BRS 264, IAC 24-Tucuruí, IAC 364-Tucuruí III and VI 98053, between meiosis and anthesis; and BRS 254, IAC-24-Tucuruí, IAC-364-Tucuruí III and VI 98053, between anthesis and physiological maturity. High temperatures reduce grain yield and yield components. The number of grains per spike is the most reduced component under heat stress. The genotypes differed in tolerance to heat stress in different developmental stages.